USE OF KETAMINE AND XYLAZINE AS GENERAL ANAESTHETICS IN DOGS - N.Alasadi, R.; Shnain, H.; H. Dawood, W. (The Iraqi Journal of Veterinary Medicine, 1990)
Ketamine Hcl 15mg/kg B.W. and xylazine 5 mg/kg B.W. have been found the most dependable doses for surgical anaesthesia in dogs. Temperature, pulse and respiratory rate were recorded under the effect of the mixture. Overdose effects and intravenous injection of the mixture proved to be safe. The mixture was used to anaesthetize immature and very young puppies as well as bitches in the late stage of the pregnancy and there was no adverse effects to these animals.